Cardiorespiratory fitness mediates cortisol and lactate responses to winter and summer marches: VO2max associated cortisol and lactate responses to marching - Pesic, Deniel; Djukic, Mirjana; Stanojevic, Ivan; Živkovic, Vladimir; Bolevich, Sergey; Bolevich, Stefani; Jakovljevic, Vladimir (Journal of Medical Biochemistry, 2023)
Background: The extent to which homeostatically regulated physiological processes (including cardiorespiratory fitness expressed as VO2max) are involved in response to physical stressors (which include acclimatization and marching) has not been studied, and we intended to make this assessment based on measured cortisol levels and blood lactate in subjects exposed to summer and winter acclimatization and marching. Methods: Two groups of young men with poor (PCF; n=9) and better physical condition (GCF; n=21), corresponding to the VO2max threshold of 40mL O2/kg/min, marched 15 km at an average speed of 6-7 km/h, in winter (5˚C) and in summer (32˚C). Blood sampling was performed in the morning hours (10 am) before and immediately after the march. At the same time, the participants’ pulses had not yet settled, and cortisol and lactate analyses were performed using routine methods. Results: Basal cortisol was significantly elevated at 5°C in the PCF group. After marching, cortisol decreased substantially in both groups at 5°C. Basal and post-marching cortisol levels were significantly elevated only at 32°C in the GCF group. Conclusions: Cold is more stressful to the body than heat and physical activity reduces cold-related stress, regardless of fitness. Individuals with poorer fitness are more susceptible to cold or heat stress. Only individuals with better physical fitness (associated with lower cortisol levels) had higher lactate levels at baseline and after marching at 32 °C, confirming that their energy metabolism is more dependent on lactate metabolism and that they are less stressed under these conditions.